Identifying Components of Positive Youth Development in Multicultural Contexts - Saadati, Nadereh; Çobanoglu, Necati; Coelho, Olga; Saadati, Seyed Amir (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The objective of this study was to explore and identify the key components of Positive Youth Development (PYD) as experienced by adolescents and young adults in multicultural contexts.Methods and Materials: This qualitative study employed a purposive sample of 25 participants aged 15–24 years from Michigan, representing diverse cultural and ethnic backgrounds. Data were collected through semi-structured interviews focused on identity formation, resilience, cultural interaction, and future readiness. Interviews, lasting between 45 and 75 minutes, were transcribed verbatim and analyzed using thematic analysis with the aid of NVivo 14 software. Data collection continued until theoretical saturation was reached. To enhance trustworthiness, peer debriefing, member checking, and reflexive memoing were incorporated throughout the research process.Findings: The analysis revealed four overarching themes and multiple subthemes that collectively represent the components of PYD in multicultural contexts. The first theme, personal growth and identity formation, emphasized self-awareness, resilience, and bicultural identity negotiation. The second, social relationships and support networks, included family support, peer bonds, mentorship, and community engagement. The third, cultural competence and diversity adaptation, reflected intercultural sensitivity, inclusivity, and strategies for balancing heritage with adaptation. The fourth, skills and future readiness, highlighted educational engagement, career planning, life skills, creativity, leadership, and health behaviors. Illustrative quotations demonstrated how youth integrated internal and external assets to foster resilience, belonging, and thriving.Conclusion: The findings affirm the universality of developmental assets while underscoring their cultural variability in multicultural contexts. By situating PYD within diverse environments, this study highlights the interplay of identity, relationships, cultural competence, and future readiness in shaping youth development. The results provide valuable implications for educators, policymakers, and practitioners in designing culturally responsive and inclusive youth programs.